(untitled) (Journal of Hama University, 2021)
This research aims to study the discrepancies in the characteristics of efficient investment portfolios resulting from the adoption of different measures of risk and the impact of that reliance on the variation of those characteristics, by applying to a sample of the shares of companies listed on the Damascus Stock Exchange during the period (2/20/2019 - 3/3/2021) and to achieve this goal. Four efficient portfolio curves were formed using two models for the formation of portfolios that differ in terms of the adopted risk measure, after measuring the expected returns from the stocks nominated for investment in each of the four portfolios in addition to measuring the degree of risk associated, depending on the prices Close the shares published on the website of the Damascus Securities Exchange. The components of the portfolios of the first curve were chosen based on the (Mean - variance) model, while the components of the remaining three portfolios were chosen using the model of partial minimum momentum at three different degrees of momentum in line with different investor types, and by comparing the characteristics of the efficient portfolios resulting from the application of both. The two models clarify the variances in the characteristics of efficient investment portfolios resulting from the adoption of each measure, and then the relationship between the scale of risk used and these variations. The research reached a set of results, the most prominent of which was the difference in the components of efficient portfolios resulting from the adoption of both measures at different rates of the required return and their similarity at the maximum possible return required and the end of the selection process into a single efficient investment portfolio that suits different types of investors.